Variation of Immune Cell Responses in Humans Reveals Sex-Specific Coordinated Signaling Across Cell Types - Fragiadakis, Gabriela K.; Bjornson-Hooper, Zachary B.; Madhireddy, Deepthi; Sachs, Karen; Chen, Han; McIlwain, David R.; Spitzer, Matthew H.; Bendall, Sean C.; Nolan, Garry P. (Frontiers in Immunology, 2022)
Assessing the health and competence of the immune system is central to evaluating vaccination responses, autoimmune conditions, cancer prognosis, and treatment. With an increasing number of studies examining immune dysregulation, there is a growing need for a curated reference of variation in immune parameters in healthy individuals. We used mass cytometry (CyTOF) to profile blood from 86 humans in response to 15 ex vivo immune stimuli. We present reference ranges for cell-specific immune markers and highlight differences that appear across sex and age. We identified modules of immune features that suggest there exists an underlying structure to the immune system based on signaling pathway responses across cell types. We observed increased MAPK signaling in inflammatory pathways in innate immune cells and greater overall coordination of immune cell responses in females. In contrast, males exhibited stronger pSTAT1 and pTBK1 responses. These reference data are publicly available as a resource for immune profiling studies.